2019
DOI: 10.1002/app.48049
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic PVDF‐g‐PDMAPMA ultrafiltration membrane with enhanced hydrophilicity and antifouling properties

Abstract: It is easy to adsorb the pollutants from water owning to the hydrophobicity of the poly(vinylidene fluoride) (PVDF) ultrafiltration (UF) membrane. To improve the hydrophilicity of the PVDF UF membrane, a novel amphiphilic copolymer PVDF-g-poly-N-(3-dimethylaminopropyl)methacrylamide] (PDMAPMA) was developed. The amphiphilic PVDF-g-PDMAPMA was synthesized with PVDF and N-(3-dimethylaminopropyl)methacrylamide (DMAPMA) via free-radical polymerization, and characterized by Fourier transform infrared spectroscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The carbonyl (─C═O) peak assigned to ─CONH─ and ─COOR appears at 1731 and 1640 cm −1 , respectively. The peak at 1529 cm −1 is caused by N─H in‐plane bending vibration 29,31,38,39. These findings suggested that the PED and R‐PED have been successfully prepared.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The carbonyl (─C═O) peak assigned to ─CONH─ and ─COOR appears at 1731 and 1640 cm −1 , respectively. The peak at 1529 cm −1 is caused by N─H in‐plane bending vibration 29,31,38,39. These findings suggested that the PED and R‐PED have been successfully prepared.…”
Section: Resultsmentioning
confidence: 81%
“…N ‐[3‐(dimethylamino)propyl]methacryamide (DMAPMA) possesses some excellent properties such as high monomer reactivity, good water, and alcohol solubility 30 . It contains a tertiary amide group, which is hydrophilic and can be quaternized 31 . In this study, the DMAPMA and ethyl acrylate (EA) were used as the hydrophilic and hydrophobic monomer, respectively, and ethanol was used as the solvent, a copolymer (PED) was synthesized by solution polymerization, and then the PED was quaternized using 3‐chloro‐1‐propanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it increases the cleaning cost of the membrane and, finally, shortens the service life of the membrane. It is generally believed that a hydrophilic membrane could somehow overcome membrane fouling problems [4][5][6][7], because the hydrophilic membrane easily forms a hydration layer on the membrane surface that can effectively reduce the adhesion between pollutants and the membrane surface. In addition, the charge on the membrane surface is also an important factor that slows down membrane fouling [8], because some pollutants in water are charged.…”
Section: Introductionmentioning
confidence: 99%
“…The solutes such as the proteins, colloidal particles, or organic matters may deposit onto the PVDF membrane pores, cause the pore blocking and finally lower the permeation flux, and shorten membrane lifespan. Comparably, a hydrophilic membrane surface demonstrates good antifouling ability, because the good hydrophilicity helps the formation of a hydration layer on the membrane surface that may resist the contact of contaminants onto the membrane surface …”
Section: Introductionmentioning
confidence: 99%